The Influence of Capital and Business Location on Income Trader At Gajah Mada Plaza, Malang City - Isak Yudosensius Pedri Bagut; Nur Ida Iriani; Yuni Setyowati (International Research & Development for Human Beings (IRDH), 2025)
Trading is an important part of the economy, especially for traders of small and medium businesses that contribute to the growth of economic regions. This research aims to analyze the influence of capital and location business on income traders at Gajah Mada Plaza, Malang City. This research used a quantitative method with statistics analysis techniques. This research was conducted at Gajah Mada Plaza, Malang City, East Java. Time of research in progress from December 16, 2024, to January 16, 2025. The result of this research showed that business capital's influence is positive and significant to income traders, with a coefficient regression of 0.287 and a value significance of 0.001 < 0.05. Business location has a significant influence​ on income traders with a mark significance 0.001 and t count of -3,637. Capital and location variables business in a way simultaneous influential significant to income traders, with F value count by 14,896 more big from the F table 3.26 and significance 0.001. Moreover, Adequate business capital can increase productivity and income for traders, meanwhile, location-strategic businesses​ can interest customers but also bring challenges in the form of competition and costs high operational. Therefore, good capital management and choosing the right business strategy are very necessary.